First identification of Gordonia sputi in a post-traumatic endophthalmitis patient – a case report and literatures review - Wei Fang (BMC Ophthalmology, 2017)
Abstract Background We present a case of post-traumatic endophthalmitis with relatively good prognosis caused by Gordonia sputi, which, to our knowledge is the first case in the literature. Case presentation A 24 year old man, who underwent an intraocular foreign body extraction half a month before presentation in the left eye, was referred to us complaining of blurred vision and slight pain for 5 days. His first presentation showed moderate intracameral and intravitreous purulent inflammation with a best corrected vision of counting fingers. After gram staining of the intravitreous samples revealed a gram-positive bacilli infection, a combination of amikacin and vancomycin was initially injected intravitreously. The left eye kept stable for three days but deteriorated on the 4th day. On the 5th day after presentation conventional culture characterized the bacterium as an Actinomyces sp. while 16S ribosomal RNA gene sequencing confirmed it as Gordonia sputi. Thereby a complete pars plana vitrectomy combined with lensectomy and silicone oil tamponade was performed. During the surgery an intraocular irrigation with penicillin G was adopted, followed by administration of intravenous penicillin G twice one day for a week. A relatively normal fundus with slight intracameral inflammation was observed a week after the operation, and the best corrected vision recovered to 0.15. One year later his vision remained 0.1. Conclusion Gordonia sputi should be taken into consideration in patients with post-traumatic endophthalmitis especially due to foreign body penetration. Compared to conventional laboratories, molecular methods are recommended for an accurate diagnosis. A comprehensive strategy of antimicrobial agents and vitrectomy may render a satisfactory result.